The Effect of Training, Competence and Work Discipline on Teacher Performance in State SLB Jambi Province - Alfiana Hanifah; Muhammad Sofwan; Aprliitzavivaryati Aprliitzavivaryati (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to determine the effect of training on teacher performance at special schools (SLB) in Jambi Province. To determine the influence of competence on teacher performance at special schools (SLB) in Jambi Province. To determine the Influence of Work Discipline on Teacher Performance at Special Schools (SLB) in Jambi Province. This research method is included in survey research with a quantitative approach. The data collection technique used is a questionnaire. The source of research data is primary data, namely questionnaires and secondary data, namely related articles. The results of this study indicate that the Training influential positive and significant to performance of State Special Needs School teachers in the East Jambi Province with The value obtained from t statistics is 1.981 > 1.96 and the P Value is is 0.048 more small from 0.05. Then Competence influential positive and significant to performance of State Special Needs School teachers in the East Jambi Province with The value obtained for t statistics is 2.116 > 1.96 and the P Value is is 0.035 more small from 0.05. Discipline Work influential positive and significant to Performance of State Special School Teachers in East Jambi Province with The value obtained is t statistics 5.020 > 1.96 and the P Value is is 0.000 more small from 0.05.